Distributions of Sasang constitutions and six syndromes in patients with functional dyspepsia and healthy subjects - Cho, Junghyo; Ahn, Yochan; Lee, Dongsoo; Son, Changgue (Journal of Traditional Chinese Medicine, 2013)
OBJECTIVE： To investigated the characteristics of patients with functional dyspepsia（FD） in terms of Sasang constitutional medicine.METHODS： A total of 116 patients with FD were recruited based on diagnosis by gastroscopy and symptomatic measurements. The distributions of Sasang constitutions and six syndromes in terms of TKM theory in the patients was compared with those from 1423 healthy subjects.RESULTS： The distribution of Sasang constitutions for the patients with FD significantly differed from that for healthy subjects, especially among women;36.7% vs 45.6% for Taeumin, 28.9% vs 33.9% for Soumin, and 34.4% vs 20.4% for Soyangin. Our results assumed a high prevalence in Soyangin women（around 1.7 folds）, and Soumin（45.2%）, inparticular, had a high prevalence of ＂deficiency and coldness of spleen and stomach＂ compared with Taeumin（14.9%） and Soyangin types（15.7%）.CONCLUSION： This study identified a trend for the frequency of FD and the Sasang constitutions. The findings may provide new ideas for the study of prevention and management of FD.